A Course in English Communication: For the Learners of English as a Second Language
With the increasing awareness of the importance of English as a global link language and the widespread use of the Internet and the globalization of business and education, the need for learning English effectively is being felt more than ever before. This international awakening has spurred nations like China and Russia that kept away from English in the past to educate their populations in the English language. In India too, there is a renewed interest in learning English for communication. This book takes the most pragmatic and current approach to the teaching and learning of English which offers learners ready-to-use expressions in their day-to-day communication. The book offers conversations in various social contexts, in formal and informal situations, and lists in an exhaustive way all the expressions used within the particular communicative function. In addition, there are exercises at the end of each unit which provide the learners an opportunity to go through the actual use of those expressions, thereby enhancing their confidence to use English. Designed primarily as a text in communicative or functional English, this book should also be useful to all those who wish to improve their English for socially appropriate communication. Key Feature Provides learners with ready-to-use and socially appropriate expressions through conversations. Presents a full range of expressions for choice within the language functions such as requests, suggestions, asking and giving opinions, asking and giving advice, and agreeing and disagreeing. Offers practice opportunity through exercises at the end of each unit. Brings communication in English within the reach of all learners through steps like read-practice-develop-use.